Phylogenetic position of Kinnareemimus khonkaenensis (Dinosauria: Theropoda: Ornithomimosauria) from the Lower Cretaceous of Thailand - Samathi, Adun (Zootaxa, 2024)
A small-bodied ornithomimosaur, Kinnareemimus khonkaenensis Buffetaut, Suteethorn, and Tong 2009, from the Lower Cretaceous Sao Khua Formation of northeastern Thailand was first reported in 1995, then named in 2009. It is the only report of this group in Southeast Asia and was concluded to be a member of Ornithomimosauria, more derived than Harpymimus and Garudimimus but more basal than Archaeornithomimus. Since then, a few published studies have analyzed the phylogenetic position of Kinnareemimus but failed to find it within the clade Ornithomimosauria. Here, the phylogenetic analyses for assessing the relationships of Kinnareemimus within Ornithomimosauria were performed. The results suggested it might be a basal ornithomimosaur or belongs to the subclade Deinocheiridae. Kinnareemimus shares with deinocheirids the proximally projected cnemial crest and the shape of the fibula in proximal view. Its metatarsal III shows subarctometatarsalian condition with metatarsal III pinched between II and IV but visible in anterior view proximally, which might have evolved independently from other ornithomimids. However, the basal position of Kinnareemimus could also be due to the immaturity and the incomplete nature of this animal.